The activation of the Euro-Algerian partnership as a mechanism to integrate into the global economy - Allaoui, Mohamed elhassen; Boukhari, Abdelhamid (Dirassat Journal Economic Issue, 2017)
All countries aim to improve their integration in the global economy specially with the appearance of globalization challenges. There are many ways to achieve this purpose, one of them the membership in regional trade agreements as Mediterranean country Algeria signed the Euro- Algerian partnership convention with the E.U in order to increase its benefits and decrease some disadvantages of trade liberalization . so what are the effects of this convention and the means to improve its effectiveness .